Combining ability analysis among Sudanese and IITA maize germplasm at Gezira Research Station - Meseka, S.K.; Ishaaq, J. (2012)
Objective: A study was conducted to estimate combining ability among four introduced drought tolerant maize (Zea mays L.) inbred lines and five local open pollinated varieties (OPVs) in Line x Tester mating design. Methodology and results: The experiment was arranged in 5 x 5 alpha lattice with three replications conducted at Gezira Research Station (GRS), Sudan, in 2008 and 2009. Significant differences were detected among hybrids for all measured traits. Combining ability analysis showed that non-additive gene effects were important for inheritance of all traits except ear length which was controlled by additive gene effects. General combining ability (GCA) had the highest contribution to total variation of plant height, ear height, and grain yield, whereas specific combining ability (SCA) had the highest contributions to days to 50% anthesis. Among the testers, Pop10 was the best general combiner for grain yield across the two years. (Mugtama-45 x Pop10), (Hudeiba-1 x Pop10) and (Giza-2 x 1824) exhibited significant SCA effects for grain yield. Regression of grain yields of hybrids and OPVs on their ear length revealed that grain yield accounted for 62% of the total variability. The top-cross hybrids had higher grain yields and relatively longerears than the local OPVs. Conclusion and application: This study suggests that Pop10 was the best general combiner for grain yield and could be used for developing hybrids in the Sudan.